Supersaturated proteins are enriched at synapses and underlie cell and tissue vulnerability in Alzheimer's disease. Issue 11 (November 2019) - Freer, Rosie; Sormanni, Pietro; Ciryam, Prajwal; Rammner, Burkhard; Rizzoli, Silvio O.; Dobson, Christopher M.; Vendruscolo, Michele
Abstract: Neurodegenerative disorders progress across the brain in characteristic spatio-temporal patterns. A better understanding of the factors underlying the specific cell and tissue vulnerability responsible for such patterns could help identify the molecular origins of these conditions. To investigate these factors, based on the observation that neurodegenerative disorders are closely associated with the presence of aberrant protein deposits, we made the hypothesis that the vulnerability of cells and tissues is associated to the overall levels of supersaturated proteins, which are those most metastable against aggregation. By analyzing single-cell transcriptomic and subcellular proteomics data on healthy brains of ages much younger than those typical of disease onset, we found that the most supersaturated proteins are enriched in cells and tissues that succumb first to neurodegeneration. Then, by focusing the analysis on a metastable subproteome specific to Alzheimer's disease, we show that it is possible to recapitulate the pattern of disease progression using data from healthy brains. We found that this metastable subproteome is significantly enriched for synaptic processes and mitochondrial energy metabolism, thus rendering the synaptic environment dangerous for aggregation. The present identification of protein supersaturation as a signature of cell and tissue vulnerability in neurodegenerative disorders could facilitate the search for effective treatments by providing clearer points of intervention. Abstract : Biophysics; Neuroscience; Alzheimer's ​disease; Protein supersaturation; Neuronal vulnerability; Protein homeostasis; Neurodegenerative diseases